2010
DOI: 10.5367/000000010791305626
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Externalities in Tourism: A Dynamic Optimal Taxation Approach

Abstract: The paper studies optimal taxation (subvention) when tourism is associated with "multiple externalities", using a simple dynamic model of a small open economy, which is completely specialized in the production of tourism services and populated by a large number of intertemporally optimizing agents.Depending on the volume of tourism production, the externality can be either positive or negative. We show that the first best optimum, achieved by a central planner, recognizing the externality, can be replicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Despite the potential economic benefits of tourism, a number ofstudies have notednegative externalities of tourism development, such asenvironmental degradation because of overexploitation of natural resources (Capó et al, 2007;Schubert, 2010), economic impoverishment of the resident population (Chao et al, 2006;Nowak et al, 2003), Dutch disease effects 1 (Capó et al, 2007;Holzner, 2005), loss of cultural and social values of the host community (Cooper et al, 1993), and the highly volatile nature of tourism receipts (Ghalia and Fidrmuc, 2016). 2 In a similar vein, and observed that tourism activity negatively affected Chinese economic growth, principally because of weak institutions, price volatility and the crowding out of human capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the potential economic benefits of tourism, a number ofstudies have notednegative externalities of tourism development, such asenvironmental degradation because of overexploitation of natural resources (Capó et al, 2007;Schubert, 2010), economic impoverishment of the resident population (Chao et al, 2006;Nowak et al, 2003), Dutch disease effects 1 (Capó et al, 2007;Holzner, 2005), loss of cultural and social values of the host community (Cooper et al, 1993), and the highly volatile nature of tourism receipts (Ghalia and Fidrmuc, 2016). 2 In a similar vein, and observed that tourism activity negatively affected Chinese economic growth, principally because of weak institutions, price volatility and the crowding out of human capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5. Alternative models often used to investigate the relationship between tourism and growth are based upon dynamic models of trade (Hazari and Sgro, 1995;Schubert et al, 2011) or traditional growth-type models (Hernandez-Leon, 2013;Schubert, 2010). 6.…”
Section: Fundingmentioning
confidence: 99%
“…Based on this principle, price-based instruments are advocated to internalise adverse environmental impacts, lower tourism capacity, and increase longterm societal welfare. For instance, Lozano, Gómez, and Rey-Maquieira (2008), Piga (2003), andSchubert (2010) propose theoretical models based on partial or general equilibrium frameworks to support overnight-stay tax, tourism tax in general (payable by tourists), and land-use tax, respectively.…”
Section: Environmental Policy and Governancementioning
confidence: 99%